A new Middle–Late Jurassic flora and hot spring chert deposit from the Deseado Massif, Santa Cruz province, Argentina - Channing, Alan Ernest (2007)
We present an initial report of a well-preserved and relatively diverse Gondwanan plant assemblage from Bahía Laura Group, Chon Aike Formation strata of the Estancia Flecha Negra area, central-western region of the Deseado Massif, Santa Cruz province, Patagonia, Argentina. The locality contains the first richly fossiliferous chert with a diverse and well-preserved plant assemblage reported from the Mesozoic which is demonstrably associated with hot spring activity. A compression flora and petrified forest contained in associated clastic and volcaniclastic environments provide an indication of regional plant diversity during this as yet poorly represented stratigraphic interval.